Precision positioning with commercial smartphones in urban environments - Paiva, Sara (EAI/Springer innovations in communication and computing, 2021)
This book discusses recent technologies and case studies that aim to enhance positioning obtained with commercial smartphones in urban environments, overcoming difficulties with GPS. The authors provide insight into recent trends and innovation on technologies, solutions and approaches to overcome GPS issues in urban environments, due to the existence of a big number of buildings. Topics include security and legal aspects related to positioning systems, the usage of crowdsourcing approaches to enhance positioning, location-based services, proximity based-social networking, satellite navigation and Bluetooth low-energy based systems. The book provides important information for developers that intend to make use of precise positioning for the purpose of commercial applications as well as for research and innovation. Discusses technologies that enhance positioning obtained with commercial smartphones in urban environments; Presents innovations to overcome GPS issues in urban environments caused by dense cities; Includes applications of precise positioning, including their security issues and challenges.